DESAIN DAN UJI COBA MEDIA PEMBELAJARAN WEBLOG BERBASIS PROBLEM BASED LEARNING PADA MATERI HIDROKARBON - Wulan Permata Sari; Heppy Okmarisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to produce a problem-based learning weblog on hydrocarbons. The research method used is Research and Development (RnD), the research model used is according to Borg and Gall which is limited to the 5th stage. The instrument used in this study was a questionnaire using a Rating scale with five ratings arranged in the form of a checklist. The results of this study are in the form of a problem-based learning weblog on hydrocarbon material called let's learn. The weblog based on problem based learning on hydrocarbon material is declared feasible based on the results of the study, the percentage of assessment on media validation by material experts is 91% and media experts is 83.33% with very valid assessment criteria, the percentage of assessment on the teacher practicality test is 86.66% with very practical assessment criteria, and student response test of 83.3% stated very good.